The P300 Auditory Evoked Potential in Cochlear Implant Users: A Scoping Review - Amaral, Maria Stella Arantes do; Zamberlan-Amorin, Nelma Ellen; Mendes, Karina Dal Sasso; Bernal, Sarah Carolina; Massuda, Eduardo Tanaka; Hyppolito, Miguel Angelo; Reis, Ana Cláudia Mirândola Barbosa (International Archives of Otorhinolaryngology, 2022)
Introduction The P300 auditory evoked potential is a long-latency cortical potential evoked with auditory stimulation, which provides information on neural mechanisms underlying the central auditory processing.Objectives To identify and gather scientific evidence regarding the P300 in adult cochlear implant (CI) users.Data Synthesis A total of 87 articles, 20 of which were selected for this study, were identified and exported to the Rayyan search software. Those 20 articles did not propose a homogeneous methodology, which made comparison more difficult. Most articles (60%) in this review compare CI users with typical hearing people, showing prolonged P300 latency in CI users. Among the studies, 35% show that CI users present a smaller P300 amplitude. Another variable is the influence of the kind of stimulus used to elicit P300, which was prolonged in 30% of the studies that used pure tone stimuli, 10% of the studies that used pure tone and speech stimuli, and 60% of the studies that used speech stimuli.Conclusion This review has contributed with evidence that shows the importance of applying a controlled P300 protocol to diagnose and monitor CI users. Regardless of the stimuli used to elicit P300, we noticed a pattern in the increase in latency and decrease in amplitude in CI users. The user's experience with the CI speech processor over time and the speech test results seem to be related to the P300 latency and amplitude measurements.
Keywords: auditory evoked potential; cochlear implant; electrophysiology; neuronal plasticity; audiology